Mortality due to ectopic pregnancy revealed by police surgeon - Sharma, Naveen; Yadav, Naveen (International Journal of Research in Medical Sciences, 2023)
A pregnancy is said to be ectopic when implantation of fertilized ovum occurs other than uterine cavity. The incidence of ectopic pregnancy is increasing globally over time and carries significant maternal mortality due to the risk of rupture of ectopic pregnancy. Ruptured ectopic pregnancy is a life threatening surgical emergency. Usually, any abnormality in tubal morphology or function may lead to tubal ectopic pregnancy. Also an altered hormonal ratio (i.e. estrogen/progesterone) may affect tubal motility and cause ectopic pregnancy. To make diagnosis of ectopic pregnancy merely on the basis of symptoms is difficult and challenging task for clinician due to its non-specific clinical manifestations and such cases can be present with normal intrauterine pregnancy. Authors report a case of ruptured tubal ectopic pregnancy which remained undiagnosed clinically because clinician refer the patient to higher center for ultrasonography to confirm or rule out the ectopic pregnancy as there was non-availability of bed side ultrasonography machines in rural health care centers in developing countries like our country. but patient died in ambulance before reaching to higher center. The autopsy revealed 1.5-liter fluid and clotted blood in the peritoneal cavity. The right fallopian tube was bulged along with a tear evident on the anterior and superior aspect. Complete dissection revealed a gestational sac of diameter 7.5 cm containing a foetus and placenta. All other organs were pale and normal. The uterine cavity was found empty. The cause of death was attributed to ruptured ectopic pregnancy. This case emphasizes the fact that “health for all” and importance of the availability of various radiological investigations including ultrasonography, prompt diagnosis, laparoscopic management are the minimal demand of rural health care centers which play a major role in saving of life. Furthermore, this report envisions benefitting clinicians and autopsy surgeons facing similar cases in their practice. Finally, this case is another addition in maternal mortality data.